Hamiltonian form of the mechanics of dissipative systems and some analogues of the conservation laws of the noether - Касьянов, В. О. (Proceedings of National Aviation University (archive), 2002)
The Hamiltonian mechanics of dissipative systems with dysgate, proportional to the first and second stages of generalized speed are considered.